Cláusulas de apertura al derecho internacional de los Derechos Humanos: constituciones iberoamericanas - León Bastos, Carolina; Wong Meraz, Víctor Alejandro (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2016)
Ibero-American Constitutions show their concern to recognize and guarantee basic human rights to all their subjects, to which purpose they include in their terms and conditions special terms where they acknowledge the openness of their rights. To such extent every state chooses what it sees as main features and principles, which in this piece of work we call Basic Statements of the Opening Clauses. A compared analysis starts with such points which appear in practically every constitutional text in Latin America.
Keywords: Human Rights; Constitution; opening clauses; international treaties; human dignity.